2022
DOI: 10.3389/fimmu.2022.953949
|View full text |Cite
|
Sign up to set email alerts
|

mRNA vaccination drives differential mucosal neutralizing antibody profiles in naïve and SARS-CoV-2 previously-infected individuals

Abstract: Two doses of BNT162b2 mRNA vaccine induces a strong systemic SARS-CoV-2 specific humoral response. However, SARS-CoV-2 airborne transmission makes mucosal immune response a crucial first line of defense. Therefore, we characterized SARS-CoV-2-specific IgG responses induced by BNT162b2 vaccine, as well as IgG responses to other pathogenic and seasonal human coronaviruses in oral fluid and plasma from 200 UK healthcare workers who were naïve (N=62) or previously infected with SARS-CoV-2 (N=138) using a pan-coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…We found that spike-specific mucosal antibodies were low after the 3rd mRNA vaccine dose and similar between SARS-CoV-2 naive and previously-infected individuals. We and others have shown that mucosal IgA is induced by mRNA vaccines in those with a history of prior SARS-CoV-2 (23,24), so this finding was unexpected, and is perhaps explained by our cohort being enriched for previously-infected healthcare workers with low mucosal immunity and therefore at risk of breakthrough infection. We have also previously noted a waning of mucosal IgA over 9 months after SARS-CoV-2 infection (25) and the time to first infection in our previously-infected cohort was much longer.…”
Section: Discussionmentioning
confidence: 72%
“…We found that spike-specific mucosal antibodies were low after the 3rd mRNA vaccine dose and similar between SARS-CoV-2 naive and previously-infected individuals. We and others have shown that mucosal IgA is induced by mRNA vaccines in those with a history of prior SARS-CoV-2 (23,24), so this finding was unexpected, and is perhaps explained by our cohort being enriched for previously-infected healthcare workers with low mucosal immunity and therefore at risk of breakthrough infection. We have also previously noted a waning of mucosal IgA over 9 months after SARS-CoV-2 infection (25) and the time to first infection in our previously-infected cohort was much longer.…”
Section: Discussionmentioning
confidence: 72%
“…We found that spike-specific mucosal antibodies were low after the 3rd mRNA vaccine dose and similar between SARS-CoV-2 naive and previously-infected individuals. We and others have shown that mucosal IgA is induced by mRNA vaccines in those with a history of prior SARS-CoV-2 24 , 25 , so this finding was unexpected and is perhaps explained by our selection of a cohort of healthcare workers who experienced an omicron infection, thereby potentially enriching for previously-infected individuals at increased risk of breakthrough infection due to low mucosal immunity. We have also previously noted a waning of mucosal IgA over 9 months after SARS-CoV-2 infection 26 and the time to first infection in our previously-infected cohort was much longer.…”
Section: Discussionmentioning
confidence: 79%
“…Our Omicron BA.1 attack rate estimated by a combination of RT-PCR and serology is very similar to those based on serological modelling from urban (58%) and rural (65%) South Africa in the PHIRST-C cohorts 23 . Further exploration of immune correlates of protection in our cohort will be valuable, with a particular focus on mucosal immunity, which is induced by infection but less consistently by parenteral vaccines 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%